WEFE nexus management plan for sustainable development and gender equity in the Matmata region, SE Tunisia - Besser, Houda; Mahjoubi, Afef; Theodotou Schneider, Xenia; Abdelli, Fethi; Caporali, Enrica; Rizzo, Bianca Maria; Nardi, Fernando; Ouessar, Mohamed (Frontiers in Water, 2025)
IntroductionClimate variability and socio-environmental challenges are often assessed separately, overlooking their interdependencies. This siloed management approach may mitigate one issue while inadvertently intensifying others. The Water, Energy, Food, and Ecosystem (WEFE) nexus approach provides, however, a holistic framework for understanding these interconnected systems and promoting sustainable resource management with particular attention to gender mainstreaming and social inequality.MethodologyThis paper establishes, consequently, a baseline study for applying the WEFE nexus transition scheme in the Matmata region, a semi-arid area characterized by an important rural exodus, limited water resources, and monoculture agrosystems. Using a participatory, community-driven approach, data were collected during field surveys, face-to-face meetings, multi-stakeholder dialogue, the Delphi method, focus group discussions, and the nominal group technique. Qualitative data were statistically treated using inter-rater coding. Findings highlight sociocultural barriers as a major constraint to women's effective participation in the Nexus Ecosystem Laboratory (NEL) of Matmata. Economic dependency stemming from family agricultural unpaid work restricts their inclusion in the decision-making process and ownership rights. Their growing awareness of nature-based solutions and motivation to initiate micro-projects that valorize local natural and cultural assets align with the nexus transition schemes.Results and discussionPromoting institutional arrangements and enhancing gender inclusion are pivotal for driving systemic transformation. The research emphasizes that fostering gender equity is integral to economic sustainability. The successful shift toward the WEFE nexus governance approach must incorporate overlooked social dimensions and invest in community-based strategies, expanding the nexus toolkits for a flexible and adaptive approach.